Assessing the quality of mental health rehabilitation services - Killaspy, H. (Die Psychiatrie, 2015)
Background: Mental health rehabilitation services focus on people with severe and complex problems that impair their function and make them potentially vulnerable to exploitation and abuse. They require longer term treatment and support from a range of inpatient and community services that hold therapeutic optimism and adopt a recovery orientation. Aims: In recent years, specific tools and processes have been developed to facilitate assessment of the quality of care in services that provide rehabilitation. These include the built environments where people receive support, the therapeutic culture of these facilities, the treatments and interventions provided, the degree to which autonomy and community engagement are promoted, and the process for safeguarding human rights. Results: When local rehabilitation services are available, most people are able to be successfully discharged to the community, achieving greater independence incrementally. The quality of inpatient rehabilitation services has been shown to be positively associated with service users’ autonomy, the main aim of rehabilitation, with the most important aspect being the recovery orientation of the service.
Keywords: Quality; psychiatric; rehabilitation